Strata-based quantification of distributional uncertainty in socio-economic indicators: A comparative study of Indian states. (June 2022) - Ghosh, Abhik; Mallick, Olivia; Chattopadhay, Souvik; Basu, Banasri
Abstract: This paper reports a comprehensive study of distributional uncertainty in a few socio-economic indicators across the various states of India over the years 2001–2011. We show that the discrete generalized beta (DGB) distribution, a typical rank order distribution, provide excellent fits to the district-wise empirical data for the population size, literacy rate (LR) and work participation rate (WPR) within every states in India, through its two distributional parameters. Moreover, taking resort to the entropy formulation of the DGB distribution, a proposed uncertainty percentage (UP) unveils the dynamics of the uncertainty of LR and WPR in all states of India. We have also commented on the changes in the estimated parameters and the UP values from the years 2001–2011. Additionally, a gender based analysis of the distribution of these important socio-economic variables within different states of India has also been discussed. Interestingly, it has been observed that, although the distributions of the numbers of literate and working people has a direct (linear) correspondence with that of the population size, the literacy and work-participation rates are distributed independently of the population distributions. This detailed study of distributional uncertainty or inequalities of different socio-economic indicators within and between the various strata along with their relations with the population may help policy makers to frame better policies for a sustainable and equitable development of the country. Highlights: Distributional uncertainty in socio-economic variables in Indian states. Entropy formulation of the discrete generalized beta distribution. Proposal of uncertainty percentage, a measure defined for distributional uncertainty. Dynamics of the literacy rate (LR) and work participation rate (WPR) in Indian states. Gender based analysis of the distribution of population, LR and WPR.